2012
DOI: 10.1371/journal.pgen.1002553
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Oxidative Stress Alters a Pathway in Caenorhabditis elegans Strongly Resembling That of Bile Acid Biosynthesis and Secretion in Vertebrates

Abstract: Mammalian bile acids (BAs) are oxidized metabolites of cholesterol whose amphiphilic properties serve in lipid and cholesterol uptake. BAs also act as hormone-like substances that regulate metabolism. The Caenorhabditis elegans clk-1 mutants sustain elevated mitochondrial oxidative stress and display a slow defecation phenotype that is sensitive to the level of dietary cholesterol. We found that: 1) The defecation phenotype of clk-1 mutants is suppressed by mutations in tat-2 identified in a previous unbiased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…(2) sptl-1(−) disrupts all sphingolipid biosynthesis and its phenotype is, in contrast to elo-5(−) , highly pleiotropic, as animals showed various morphological and growth defects and die at various larval stages. (3) tat-2 does not exclusively function with mmBCFA-containing lipids; it is also a critical player in steroid metabolism as exemplified by a recent article (Liu et al, 2012). Therefore, the link between mmBCFA and sphingolipids through their interactions with tat-2 could be indirect and the partial suppression of sptl-1(−) by tat-2(−) could be due to suppression of mmBCFA-unrelated functions of sphingolipids.…”
Section: Methodsmentioning
confidence: 99%
“…(2) sptl-1(−) disrupts all sphingolipid biosynthesis and its phenotype is, in contrast to elo-5(−) , highly pleiotropic, as animals showed various morphological and growth defects and die at various larval stages. (3) tat-2 does not exclusively function with mmBCFA-containing lipids; it is also a critical player in steroid metabolism as exemplified by a recent article (Liu et al, 2012). Therefore, the link between mmBCFA and sphingolipids through their interactions with tat-2 could be indirect and the partial suppression of sptl-1(−) by tat-2(−) could be due to suppression of mmBCFA-unrelated functions of sphingolipids.…”
Section: Methodsmentioning
confidence: 99%
“…This picture is further complicated by the fact that disruption of the worm electron transport chain at different places can extend lifespan but have different associated phenotypes 108 . The same study showed that ROS signaling is involved, but in a distinct mechanism that incorporates bile acid-like mediators which exert hormonal effects 109 .…”
Section: Retrograde Response In Other Organismsmentioning
confidence: 98%
“…Another engages the mitochondrial unfolded protein response and the transcription factors UBL-5 and DVE-1 (Durieux, et al, 2011), while the third is mediated by the predicted homeobox transcription factor CEH-23 (Walter, et al, 2011). The phenotypes associated with the lifespan extension afforded by mitochondrial dysfunction in the worm can be varied (Yang and Hekimi, 2010), and they can incorporate hormonal effects by bile acid-related species (Liu, et al, 2012). Similar to the worm studies, knockdown of respiratory chain components in Drosophila also extends lifespan (Copeland, et al, 2009), as does defective coenzyme Q synthesis (Liu, et al, 2011), but the signaling pathways are not known.…”
Section: Retrograde Response In Other Organismsmentioning
confidence: 99%